Food safety in hospital: knowledge, attitudes and practices of nursing staff of two hospitals in Sicily, Italy - La Guardia Maurizio; Giammanco Marco; Giammanco Santo; Casuccio Alessandra; Buccheri Cecilia; Mammina Caterina (BMC, 2007)
Abstract Background Food hygiene in hospital poses peculiar problems, particularly given the presence of patients who could be more vulnerable than healthy subjects to microbiological and nutritional risks. Moreover, in nosocomial outbreaks of infectious intestinal disease, the mortality risk has been proved to be significantly higher than the community outbreaks and highest for foodborne outbreaks. On the other hand, the common involvement in the role of food handlers of nurses or domestic staff, not specifically trained about food hygiene and HACCP, may represent a further cause of concern. The purpose of this study was to evaluate knowledge, attitudes, and practices concerning food safety of the nursing staff of two hospitals in Palermo, Italy. Association with some demographic and work-related determinants was also investigated. Methods The survey was conducted, by using a semi-structured questionnaire, in March-November 2005 in an acute general hospital and a paediatric hospital, where nursing staff is routinely involved in food service functions. Results Overall, 401 nurses (279, 37.1%, of the General Hospital and 122, 53.5%, of the Paediatric Hospital, respectively) answered. Among the respondents there was a generalized lack of knowledge about etiologic agents and food vehicles associated to foodborne diseases and proper temperatures of storage of hot and cold ready to eat foods. A general positive attitude towards temperature control and using clothing and gloves, when handling food, was shared by the respondents nurses, but questions about cross-contamination, refreezing and handling unwrapped food with cuts or abrasions on hands were frequently answered incorrectly. The practice section performed better, though sharing of utensils for raw and uncooked foods and thawing of frozen foods at room temperatures proved to be widely frequent among the respondents. Age, gender, educational level and length of service were inconsistently associated with the answer pattern. More than 80% of the respondent nurses did not attend any educational course on food hygiene. Those who attended at least one training course fared significantly better about some knowledge issues, but no difference was detected in both the attitude and practice sections. Conclusion Results strongly emphasize the need for a safer management of catering in the hospitals, where non professional food handlers, like nursing or domestic staff, are involved in food service functions.